Assessment of knowledge, perception and uptake of screening for cardiovascular disease risk factors among traders in an urban market setting in Enugu, Nigeria: a cross-sectional study - Udeh, Susan C.; Aniwada, Elias C.; Nwazulu, Blessing H.; Udeh, Simon C.; Obi, Daniel C.; Ike-Samuel, Ngozika S.; Ngele, Louis N. (International Journal Of Community Medicine And Public Health, 2025)
Background: Cardiovascular diseases (CVDs) remain the leading cause of mortality globally, with disproportionate impacts in low- and middle-income countries like Nigeria. Traders, a key economic group, face heightened CVD risks due to occupational and lifestyle factors. This study assessed the knowledge, perception, and uptake of screening for CVD risk factors among traders in Ogbete Main Market, Enugu, Nigeria. Methods: A cross-sectional study was conducted among 363 traders selected through stratified random sampling. Data was collected using the Heart Disease Knowledge Questionnaire (HDKQ). Data was analyzed using SPSS version 22. Results: Participants had good knowledge of CVD risk factors (63.9). Hypertension (97.3%) and unhealthy diets (85.4%) were the most recognized risk factors, but gaps were evident in the understanding of obesity (43.5%) and physical inactivity (44.9%). Positive perception was observed in 58.1% of participants. Screening rates were low despite good knowledge and positive perceptions. Blood pressure screening was reported by 67.2%, but cholesterol (4.7%) and BMI (2.2%) screenings were alarmingly rare. Conclusions: The findings highlight significant gaps in the uptake of CVD screening among traders, despite moderate-to-good knowledge and perception levels. Targeted interventions, are needed to address these barriers.